2016
DOI: 10.1152/ajpgi.00021.2016
|View full text |Cite
|
Sign up to set email alerts
|

Role of apoptotic hepatocytes in HCV dissemination: regulation by acetaldehyde

Abstract: Alcohol consumption exacerbates hepatitis C virus (HCV) pathogenesis and promotes disease progression, although the mechanisms are not quite clear. We have previously observed that acetaldehyde (Ach) continuously produced by the acetaldehyde-generating system (AGS), temporarily enhanced HCV RNA levels, followed by a decrease to normal or lower levels, which corresponded to apoptosis induction. Here, we studied whether Ach-induced apoptosis caused depletion of HCV-infected cells and what role apoptotic bodies (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 62 publications
4
34
0
1
Order By: Relevance
“…Therefore, these cells do not produce measurable amount of Ach. To recapitulate EtOH metabolism in hepatocytes, we exposed the cells to an artificial AGS that continuously generates physiological amounts of Ach (Ganesan et al., , ). HCV‐infected cells were exposed either to EtOH (in which case, mainly ROS were generated via CYP2E1‐mediated metabolism) or to AGS.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these cells do not produce measurable amount of Ach. To recapitulate EtOH metabolism in hepatocytes, we exposed the cells to an artificial AGS that continuously generates physiological amounts of Ach (Ganesan et al., , ). HCV‐infected cells were exposed either to EtOH (in which case, mainly ROS were generated via CYP2E1‐mediated metabolism) or to AGS.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the association of ALDH genotype and viral hepatitis at the molecular level remains largely unexplored. The major difficulty is a lack of valid models in which a liver can support viral infection and alcohol metabolism that resembles liver injury caused by alcohol consumption and viral infection in alcoholic patients with chronic hepatitis C [41]. Our previous work demonstrated that alcohol-fed Aldh2 -/mice were less sensitive to concanavalin A-induced T-cell hepatitis than wild-type mice [42].…”
Section: Aldh and Viral Liver Diseasesmentioning
confidence: 99%
“…The antiviral activity of the ADH/ALDH pathway may be compromised even by a physiological alcohol concentration in alcoholic individuals, likely through alcohol-ROL metabolic competition [38]. A mechanism for acetaldehyde exposure-induced liver injury in HCV-infected cells was proposed by Ganesan et al, who found that acetaldehyde is continuously generated in the acetaldehyde-generating system (AGS), resulting in a transient increase in HCV RNA, which subsequently recedes to normal or lower levels when a significant number of HCV-infected cells undergo apoptosis [41]. Acetaldehyde is also associated with higher miR-122 and miR-34a expression in HCV-infected hepatocytes, leading to higher HCV replication, and consequently, apoptosis due to robust HCV replication and accumulation of viral products.…”
Section: Aldh and Viral Liver Diseasesmentioning
confidence: 99%
“…To overcome this limitation, we treated RLW cells with an acetaldehyde-generating system (AGS), which contains yeast ADH as a source of enzyme, nicotinamide adenine dinucleotide (NAD) as a co-factor, and 50 mM ethanol (EtOH) (substrate for ADH), and continuously produces physiologically relevant amounts of acetaldehyde (Ach) without toxic effects. We have characterized and successfully used these cells and AGS for HCV-based ethanol in vitro studies [24,25]. The downstream effects of AGS were validated by experiments on ethanol-treated primary hepatocytes.…”
Section: Cells and Treatmentsmentioning
confidence: 99%
“…Here, we asked the question as to whether this ABHep formation from infected hepatocytes is beneficial or harmful for the liver. To mimic pro-apoptotic effects of AGS treatment, we generated ABHep from uninfected and HIV-infected RLW cells (apoptotic bodies control (ABcntr) and apoptotic bodies HIVinfected (ABHIV)) as described and characterized earlier [25]. These ABHep were incubated with MDMs for two hours and then inflammasome activation was measured based on NLRP3, caspase-1, IL-1β, and IL-18 mRNA expressions.…”
Section: Hepatocyte-derived Apoptotic Bodies (Abhep) and Hiv Infectionmentioning
confidence: 99%